Mineralogical composition of African dust delivered by red rains over northeastern Spain - Avila, a; QueraltMitjans, I; Alarcon, M (JOURNAL OF GEOPHYSICAL RESEARCH-ATMOSPHERES, 1997)
The African dust deposition, mineralogy, source regions, and influence on rain chemistry were analyzed for a site in the Montseny mountains (Catalonia, northeastern Spain) for the period August 1, 1983, through August 1, 1994. Dust deposition was highly variable: two events (collected on November 9-11, 1984, and March 22-25, 1991) accounted for 62% of the total dust input in the 38 red rain events recorded in the period. The average annual dust deposition was 5.3 g m(-2) (SE 2.6). Three source regions in the African continent were identified with back trajectory analysis: (1) Western Sahara, (2) Moroccan Atlas, and (3) Central Algeria. Events from the Moroccan Atlas predominated in terms of number of events, amount of rainfall, and dust deposition. The meteorological situations during red rains were identified: Western Sahara events occurred principally with a depression at high latitudes (50 degrees N) forming a trough in the North Atlantic, Moroccan Atlas events occurred with a depression in front of Portugal, and events from central Algeria were associated with a depression over Spain or North Africa. By order of abundance (median of n=13) the minerals identified in the dust by X ray diffraction were as follows: illite > quartz > smectite > palygorskite > kaolinite > calcite > dolomite > feldspars. Differences in mineralogy between source regions were significant for smectite, kaolinite, quartz, and dolomite. Smectite and kaolinite content was highest in the Algerian events, while quartz and dolomite content was lowest. Events from the Moroccan Atlas had the lowest smectite and kaolinite. The red rain soluble chemistry was clearly influenced by the dissolution of calcite (high alkalinity, calcium concentration and basic pH) and by marine components (high Na+, Cl- and Mg+2 concentrations). Because of the very alkaline character of red rains they had a strong weight on the annual mean pH of rainwater. This was reflected by the significant relationship (r=0.71, p<0.01) between the percentage of annual precipitation as red rain and annual mean precipitation pH. Red rains provided 25-45% of the annual dissolved input of the major ions in precipitation and 34% of the calcium required for helm oak (Quercus ilex L.) forest growth at the study site.
APS
Keywords: Africa; dust deposition; Montseny mountains; Quercus ilex L.